PENGARUH LITERASI KEUANGAN, KONTROL DIRI, DAN PENDAPATAN ORANGTUA TERHADAP PERILAKU KOMSUMTIF MAHASISWA MANAJEMEN KEUANGAN SYARIAH ANGKATAN 2019-2021 UIN SAYYID ALI RAHMATULLAH TULUNGAGUNG - Vernica Nikmahtu Asita; Syafrudin Arif Marah Manunggal (Jurnal Ilmiah Global Education, 2023)
The purpose of this study was to test the significant effect of financial literacy, self-control, and parental income on the consumptive behavior of Islamic Financial Management students. Batch 2019-2021 UINSayyid Ali Rahmatullah Tulungagung. This study uses a quantitative approach. The data was collected through a questionnaire method with probability sampling technique, and using a Roscoe sample of 110 respondents. Validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, T test, F test, and R2 test were used to obtain analysis of the data results. The results of this study indicate that financial literacy has no significant effect on student consumptive behavior, self-control has a significant effect on student consumptive behavior, parental income has a significant effect on student consumptive behavior. Simultaneously the influence of financial literacy, self-control, and parental income simultaneously has a significant effect on the consumptive behavior of Islamic Financial Management students Batch 2019-2021 UIN Sayyid Ali Rahmatullah Tulungagung.